An introduction to relativity - Narlikar, Jayant Vishnu, 1938- (Cambridge ; New York : Cambridge University Press, 2010)
"General relativity is now an essential part of undergraduate and graduate courses in physics, astrophysics and applied mathematics. This simple, user-friendly introduction to relativity is ideal for a first course in the subject. Beginning with a comprehensive but simple review of special relativity, the book creates a framework from which to launch the ideas of general relativity. After describing the basic theory, it moves on to describe important applications to astrophysics, black hole physics, and cosmology. Several worked examples, and numerous figures and images, help students appreciate the underlying concepts. There are also 180 exercises which test and develop students' understanding of the subject. The textbook presents all the necessary information and discussion for an elementary approach to relativity. Password-protected solutions to the exercises are available to instructors at www.cambridge.org/9780521735612"--Provided by publisher.
The special theory of relativity -- From special to the general theory of relativity -- Vectors and tensors -- Covariant differentiation -- Curvature of spacetime -- Spacetime symmetries -- Physics in curved spacetime -- Einstein's equations -- The Schwarzschild solutions -- Experimental tests of general relativity -- Gravitational radiation -- Relativistic astrophysics --Black holes -- The expanding universe -- Friedmann models -- The early universe -- Observational cosmology -- Beyond relativity.
Includes bibliographical references and index.
Keywords: General relativity (Physics)